Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1037/lhb0000226
|View full text |Cite
|
Sign up to set email alerts
|

Witnessing domestic violence during childhood is associated with psychopathic traits in adult male criminal offenders.

Abstract: While there is growing evidence that suffering physical abuse during childhood is subsequently associated with psychopathic traits in both juvenile and adult offenders, there is considerably less research on whether exposure to domestic violence as a witness, rather than as a direct victim, influences the subsequent presentation of psychopathic traits in adulthood. Accordingly, the current study examined the relationship between witnessing domestic violence during childhood (i.e., witnessing, hearing, or inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 48 publications
(71 reference statements)
0
23
0
Order By: Relevance
“…Psychopathic men and women's use of coercive control with partners is an extension of coercive familial behaviors learned during childhood and adolescence [34]. Learning of coercion occurs through both practice and modeling as witnessing domestic violence is a risk factor for the development of psychopathy [89]. Although some link coercive control to patriarchy [86], case histories of perpetrators suggest psychopathy [86,90] and women perpetrate coercive control [87,88].…”
Section: Is Psychopathy Associated With Partner Abuse?mentioning
confidence: 99%
“…Psychopathic men and women's use of coercive control with partners is an extension of coercive familial behaviors learned during childhood and adolescence [34]. Learning of coercion occurs through both practice and modeling as witnessing domestic violence is a risk factor for the development of psychopathy [89]. Although some link coercive control to patriarchy [86], case histories of perpetrators suggest psychopathy [86,90] and women perpetrate coercive control [87,88].…”
Section: Is Psychopathy Associated With Partner Abuse?mentioning
confidence: 99%
“…It was shown in a current study that "the relationship between witnessing domestic violence during childhood (i.e., witnessing, hearing, or intervening in abuse against a parent/sibling) and psychopathic traits in adulthood in a sample of 127 incarcerated male offenders." [4] These traits can evidently lead to more crimes being committed as an adult and makes them more liking to offend and reoffend in adulthood. During childhood maltreatment, which includes physical/emotional abuse and neglect, there are some risk factors that can develop psychopathic traits.…”
Section: Childhood Predictorsmentioning
confidence: 99%
“…E. A. Greenfield and N. F. Marks said that frequent experiences of psychological violence from parents-even in the absence of physical violence and regardless of whether such violence is from mothers or fathers-can place individuals' long-term mental health at risk [17]. M. Dargis and M. Koenigs concluded that witnessing domestic violence during childhood was significantly associated with the overall level of psychopathy, with a particularly strong relationship to the interpersonal/affective features of psychopathy [18]. J. Devaney said that professionals working in criminal justice organisations can and should intervene whenever they suspect that a child is being exposed to domestic violence.…”
Section: Domestic Violence Against Childrenmentioning
confidence: 99%